TITLE: ESG-BASED MANAGEMENT MODEL FOR SUSTAINABLE TRANSFORMATION OF INDUSTRIAL ECOSYSTEMS: CASE OF BUKHARA OIL REFINERY (UZBEKISTAN) - Fatkulina I.S., (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  This  article  presents  an  original  model  of  ESG-based (Environmental,  Social,  and  Governance)  management  adapted  for  industrial ecosystems in transitional economies. Using the Bukhara Oil Refinery as a case study, the paper outlines the methodology, architecture, digital integration, and the results of a  pilot  implementation.  The  model  combines  international  standards  (GRI,  ISO, TCFD),  a  step-by-step  4D  transformation  framework,  project  management  tools (PMBOK,  Agile),  and  digital  analytics  (Power  BI,  SAP).  Preliminary  results demonstrate the model’s economic, environmental, and institutional efficiency and its readiness for scaling across the national industry.